2018
DOI: 10.1002/ase.1802
|View full text |Cite
|
Sign up to set email alerts
|

Using the Jigsaw Method to Teach Abdominal Anatomy

Abstract: This study evaluates a cooperative learning approach for teaching anatomy to health science students incorporating small group and peer instruction based on the jigsaw method first described in the 1970's. Fifty-three volunteers participated in abdominal anatomy workshops. Students were given time to become an "expert" in one of four segments of the topic (sub-topics) by allocating groups to work-stations with learning resources: axial computerized tomography (CT) of abdominal structures, axial CT of abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Implementing of multimedia is believed to be able to facilitate the occurrence of meaningful learning processes and experiences for students (Maria, Rusilowati, & Hardyanto, 2019;Umachandran et al, 2019). Meaningful learning is indicated to be able to facilitate students in optimizing thinking skills (Iversen, Pedersen, Krogh, & Jensen, 2015;Korres & Tsami, 2013) which in turn will determine how he understands the concepts being studied (Kiliç & Saǧlam, 2014), especially if the concepts are very complex such as human anatomy and physiology (Himschoot, 2012;Oakes, Hegedus, Ollerenshaw, Drury, & Ritchie, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Implementing of multimedia is believed to be able to facilitate the occurrence of meaningful learning processes and experiences for students (Maria, Rusilowati, & Hardyanto, 2019;Umachandran et al, 2019). Meaningful learning is indicated to be able to facilitate students in optimizing thinking skills (Iversen, Pedersen, Krogh, & Jensen, 2015;Korres & Tsami, 2013) which in turn will determine how he understands the concepts being studied (Kiliç & Saǧlam, 2014), especially if the concepts are very complex such as human anatomy and physiology (Himschoot, 2012;Oakes, Hegedus, Ollerenshaw, Drury, & Ritchie, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, this absence has been found more often in this line of research. For example, Oakes et al (2019) found that students who participated in a jigsaw lesson did not outperform students who worked in a nonjigsaw setting, even though the jigsaw groups did show high-quality processes, and students considered the jigsaw task as beneficial and enjoyable. Furthermore, Lazonder and Harmsen (2016) stated in their meta-analysis concerning guidance in inquiry learning that guidance that is specifically focused on the process does not necessarily induce acquisition of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research demonstrated that the jigsaw method was more successful than learning in traditional cooperative groups, leading to higher academic achievement (e.g., Aronson & Patnoe, 2011; Colosi & Zales, 1998). The method ensures that group members actively take part in the group process by sharing their knowledge and discussing the content in differently composed groups (Karacop & Doymus, 2013; Oakes, Hegedus, Ollerenshaw, Drury, & Ritchie, 2019). However, these process-related benefits have been demonstrated with an older target group (i.e., university students), and it is not clear yet how the method affects younger children’s cooperative processes.…”
mentioning
confidence: 99%
“…Some researchers believe that cooperative attitudes can grow with a pattern of habituation in the learning process (Scott, 2015;Triyanto, 2018). Cooperative attitudes such as togetherness in the learning process (Hedeen, 2003;Slish, 2005), responsibilities (Bennett, 2016), perceptions of the same learning goals (Slavin, 2012), fair distribution of responsibilities (Haviz, 2015), appreciation (Oakes et al, 2019), and leadership (Bennett, 2016) always emerge and grow in student learning interactions (Karaçöp, 2016). On the contrary, these results were not found in the CG class.…”
Section: Figure 2 Cooperative Of Student Skills On Embryology Coursementioning
confidence: 99%
“…Jigsaw implementation is not mere a learning method but also an effort that can be done to measure the success of biology learning (Slavin, 2012). (Oakes, Hegedus, Ollerenshaw, Drury, and Ritchie, 2019) found that the jigsaw method increases knowledge about anatomy by involving group work, peer-led learning, minimal supervision, and leads to increased student performance and learning motivation. While other research also reports that various biology topics such as ecology (Asshoff, Düsing, Winkelmann, & Hammann, 2019;Smith & Chang, 2005), microbiology (Jasti, Hug, Waters, & Whitaker, 2014), anatomy (Koprowski & Perigo, 2000), biology developmental (Haviz, 2015) that are taught with jigsaw have a positive impact on students' understanding, interest in learning, and thinking ability including cognitive (Bennett, 2016) and metacognitive awareness (Palennari, 2016).…”
Section: Introductionmentioning
confidence: 99%